2022
DOI: 10.1002/adtp.202200169
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study between the 3D‐Liver Spheroid Models Developed from HepG2 and Immortalized Hepatocyte‐Like Cells with Primary Hepatic Stellate Coculture for Drug Metabolism Analysis and Anticancer Drug Screening

Abstract: Liver spheroids may be the best alternative models for evaluating efficacy and toxicity of the new anticancer candidates and diagnostics for hepatocellular carcinoma (HCC). Here, novel 3D-liver spheroid models are constructed from human hepatoma cells (HepG2)/ immortalized human hepatocyte-like cells (imHCs) with primary hepatic stellate cells (HSCs) coculture using the ultralow attachment technique. Spheroid morphology, HSC distribution, metabolic activity, protein expressions, and drug penetration are evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 67 publications
(98 reference statements)
0
1
0
Order By: Relevance
“…Similar observations were made by other research groups. [24,37,38] They showed that the presence of stellate cells in the structure of the aggregate facilitates its compactness. 2D and 3D cocultures of hepatocytes and endothelial cells were also presented in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Similar observations were made by other research groups. [24,37,38] They showed that the presence of stellate cells in the structure of the aggregate facilitates its compactness. 2D and 3D cocultures of hepatocytes and endothelial cells were also presented in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…The protein expression of albumin and mRNA expression of hepatocyte markers CK18 , HNF4 α, RBP4 , and CYP2E1 (with the exception of CYP3A4 ) in human 3D liver spheroids (HLS) are similar to those observed in human primary plated hepatocytes (2D) cultured for one day. In particular, the mRNA expression of CYP3A4 increased in a time-dependent manner, as HSCs could promote liver sinusoidal structure development and enhance the activity of CYP3A4 11 ( Figures 2 F and 2G).
Figure 2 Characterization of normal human liver spheroids Immunofluorescent images of spheroids stained for (A) Hepatocyte nuclear factor 4α (HNF4α), Vimentin and DAPI; or (B) CD68, NCR1, PECAM, and DAPI (scale bar = 250 μm).
…”
Section: Expected Outcomesmentioning
confidence: 98%
“…The reagent is designed to efficiently penetrate cells within a biological sample, including dense 3D structures like tumor spheroids [20,21]. Our choice was driven by the balance between methodological accessibility and the ability to compare our results with a broad range of existing literature [22]. Cells were treated with the stain solution at a concentration of 2.5 μM in the cell culture medium for 45 min.…”
Section: Hypoxia Stainingmentioning
confidence: 99%